Ferroelectric characterization of aligned barium titanate nanoﬁbres - Sá, Pedro (2013)
We report the synthesis, structural and ferroelectric characterization of continuous well-aligned nanoﬁbres of barium titanate produced by the electrospinning technique. The ﬁbres with average diameter of 150–400 nm consist of connected nanoparticles of BaTiO 3 stacked together to form the shape of a long ﬁlament. The tetragonal phase in the obtained nanoﬁbres was revealed by the x-ray diffraction and Raman spectroscopy and has been also conﬁrmed by the second harmonic generation (SHG) and piezoresponse force microscopy (PFM). The temperature dependence of the SHG in the vicinity of the paraelectric–ferroelectric phase transition suggests that barium titanate nanoﬁbres are indeed ferroelectric with an apparent glass-like state caused by metastable polar nanoregions. The existence of domain structure and local switching studied by PFM present clear evidence of the polar phase at room temperature.